Method for producing rare earth sintered magnet
By adjusting the rare earth element and B content of the R-T-B system sintered magnet raw material, controlling the grain boundary thickness, and manufacturing it in a low-oxygen environment, the problems of reduced coercive force and unstable supply of heavy rare earth elements are solved, and high-performance and stable sintered magnets are achieved.
Patent Information
- Application Number
- CN202411354641.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-09-27
- Publication Date
- 2025-03-28
AI Technical Summary
The coercive force of the existing R-T-B system sintered magnets decreases at high temperatures, causing irreversible thermal demagnetization, and the supply of heavy rare earth elements is unstable, and the price fluctuates greatly.
By adjusting the rare earth element and B content in the raw material alloy, the thickness of the grain boundary of the two grains is controlled, and the low oxygen environment is controlled during the manufacturing process to inhibit moisture from entering the raw material alloy powder to modify the grain boundary phase.
It is achieved to improve the coercive force and residual magnetic flux density of the R-T-B system sintered magnet without adding heavy rare earth elements, and to improve stability and performance.
Smart Images

Figure CN119724795A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a rare earth sintered magnet. Background Art
[0002] RTB sintered magnets (R is a rare earth element, but it must contain at least one of Nd and Pr, T is Fe and Co, and more than 90% of T is Fe by mass ratio, and B is boron) as a representative example of rare earth sintered magnets are known to be the highest performance magnets among permanent magnets. They are used in various motors such as electric vehicle (EV, HV, PHV) motors, industrial equipment motors, and home appliances. RTB sintered magnets mainly include R2T 14 The main phase of the B compound and the grain boundary phase (hereinafter sometimes simply referred to as "grain boundary") located in the grain boundary portion of the main phase. 14 The B compound is a ferromagnetic phase with a high magnetization.
[0003] RTB sintered magnets have a coercive force H at high temperature. cJ (Hereinafter sometimes referred to as "coercivity" or "H cJ ”) is reduced, resulting in irreversible thermal demagnetization. For this reason, the RTB-based sintered magnets used in electric vehicle motors have high H at high temperatures. cJ demand.
[0004] It is known that in RTB sintered magnets, if R2T 14 Part of the light rare earth elements (mainly Nd and / or Pr) contained in R in compound B is replaced by heavy rare earth elements (mainly Dy and / or Tb), which can increase the H cJ With the increase of heavy rare earth element substitution, H cJ Will also improve.
[0005] However, if R2T 14 The light rare earth elements in the B compound are replaced by heavy rare earth elements. cJ is improved, but the residual flux density B r (hereinafter referred to as "B r ”) will be reduced. In addition, due to the fact that heavy rare earth elements, especially Dy, have not only small reserves but also limited production areas, there are problems such as unstable supply and large price fluctuations. Therefore, in recent years, users have been demanding a method to increase H without using heavy rare earth elements as much as possible. cJ technology.
[0006] Patent Document 1 describes an RTB rare earth sintered magnet with reduced Dy content and improved coercivity. Compared with the commonly used RTB alloy, the composition of this sintered magnet is limited to a relatively small specific range of B content (boron composition ratio or boron concentration), and contains one or more metal elements selected from Al, Ga, and Cu. As a result, R2T is generated at the grain boundary. 17 phase, at the grain boundary by the R2T 17 The transition metal-rich phase (R6T 13 M) increases, thereby increasing H cJ .
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2013 / 008756 Summary of the invention
[0010] Problems to be solved by the invention
[0011] In order to achieve both reduced content of heavy rare earth elements and high B r and high H cJ In the rare earth sintered magnets, the technology of controlling the grain boundary between the two grains to a thicker value by relatively reducing the B content has been studied.
[0012] On the other hand, the inventors found that even if the amount of rare earth elements and the B content in the raw material alloy are adjusted to the required range, the thickness of the grain boundary between the two grains cannot be fully controlled based on the manufacturing process, and there are still cases where the magnet performance deteriorates. The inventors believe that the reason is that the grain boundary phase has changed due to the oxygen content of the rare earth sintered magnet. However, the study found that even if each process in the manufacturing stage (from the crushing process to the sintering process) is controlled in a low-oxygen environment, it is difficult to control the fluctuation of the oxygen concentration of the final rare earth sintered magnet to below 400ppm. It was later discovered that the reason is that moisture is mixed into the raw alloy powder of the rare earth sintered magnet from the environment during the manufacturing process.
[0013] The method for producing a rare earth system sintered magnet of the present invention can suppress the incorporation of moisture from the atmosphere during the production process into the raw material alloy powder of the rare earth system sintered magnet.
[0014] Technical solutions to solve problems
[0015] The method for manufacturing a rare earth sintered magnet of the present invention includes the steps of crushing a rare earth raw material alloy to prepare a powder of the rare earth raw material alloy; recovering the powder using a recovery container; supplying an oil agent to the recovery container before or after recovering the powder, or during the recovery; and adjusting the ratio of the mass of water in the oil agent supplied to the recovery container to the mass of the recovered powder in the oil agent, i.e., the water ratio, to less than 0.005%.
[0016] Effects of the Invention
[0017] According to the embodiment of the present invention, it is possible to suppress the incorporation of moisture from the environment during the manufacturing process into the raw alloy powder of the rare earth system sintered magnet. More specifically, it is possible to suppress the oxidation of the finely ground powder in the most oxidizable active state immediately after being produced by the pulverizing device by placing it in an oil solution with a controlled water content due to moisture. As a result, it is possible to realize a rare earth system sintered magnet with modified grain boundaries between two crystal grains. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1A Schematic diagram of the main phase and grain boundary phase of RTB sintered magnet.
[0019] Figure 1B for Figure 1A A further enlarged schematic diagram of the dotted rectangular area.
[0020] Figure 2 This is a schematic flow chart showing an outline of a method for producing a rare earth system sintered magnet according to an embodiment of the present invention.
[0021] Figure 3 It is a schematic diagram of a structural example of a pulverizing system according to an embodiment of the present invention.
[0022] Figure 4 Another schematic flow chart showing the outline of the method for producing a rare earth system sintered magnet according to an embodiment of the present invention.
[0023] Explanation of symbols
[0024] 12: Main phase
[0025] 14: Grain boundary phase
[0026] 14a: Two grain boundary phases
[0027] 14b: triple point of grain boundary
[0028] 100: Jet mill crushing device
[0029] 200: Cyclone separator capture device
[0030] 300: Bag filter
[0031] 400: Recycling container
[0032] 500: Oil supply device DETAILED DESCRIPTION
[0033] Hereinafter, an embodiment of the present invention will be described with respect to an RTB based sintered magnet as an example of a rare earth based sintered magnet.
[0034] It is known that in conventional RTB-based sintered magnets, when, for example, (1) the content of R (at least one of the rare earth elements, but at least one of Nd and Pr) is 27% by mass or more and 34% by mass or less of the entire RTB-based sintered magnet, (2) T is at least one selected from Fe, Co, Al, Mn and Si, and T at least contains Fe, and the content of Fe relative to the entire T is 80% by mass or more, and (3) the molar ratio of T to B ([T] / [B]) is greater than 14.0 and less than 15.0, by adding an element such as Ga, the thickness of the grain boundary between the two grains can be increased and the H can be increased. cJ .
[0035] The molar ratio of T to B ([T] / [B]) is obtained by dividing the analyzed values (mass %) of the concentrations of the elements constituting T (Fe or at least one of Co, Al, Mn, and Si and Fe) by the atomic weight of each element, and then calculating the ratio (a / b) of the total molar number of these values (a) and the analyzed value (mass %) of the B concentration divided by the molar number of the atomic weight of B (b).
[0036] The molar ratio of T to B ([T] / [B]) greater than 14.0 means that the content ratio of B is lower than R2T 14 In this case, in the RTB based sintered magnet, the main phase (R2T 14 Compared with the amount of T used to form compound B, the amount of B is relatively reduced.
[0037] Next, the basic structure of the RTB based sintered magnet will be described.
[0038] RTB sintered magnets have a structure in which the powder particles of the raw material alloy are bonded by sintering. 14 A main phase of the B compound and a grain boundary phase located at the grain boundary portion of the main phase.
[0039] Figure 1A Schematic diagram of the main phase and grain boundary phase of RTB sintered magnet. Figure 1B for Figure 1A A further enlarged schematic diagram of the dotted rectangular area. Figure 1AAs an example, an arrow with a length of 5 μm is recorded as a reference length indicating a size. Figure 1A and Figure 1B As shown, RTB sintered magnets mainly include R2T 14 The main phase 12 of the B compound and the grain boundary phase 14 located at the grain boundary portion of the main phase 12. In addition, Figure 1B As shown, the grain boundary phase 14 includes two R2T 14 The grain boundary phase 14a between two adjacent B compound particles (grains) and three or more R2T 14 The triple point 14b of the grain boundary between adjacent B compound grains.
[0040] R2T of main phase 12 14 Compound B is a ferromagnetic phase with high saturation magnetization (intensity) and anisotropic magnetic field. Therefore, in RTB based sintered magnets, by increasing the R2T 14 The presence ratio of B compounds can increase the r To improve R2T 14 The ratio of the B compound is preferably such that the R content, T content, and B content in the raw material alloy are close to R2T 14 The stoichiometric ratio of the B compound (R content: T content: B content = 2:14:1). 14 When the B content or R content of the B compound is lower than the stoichiometric ratio, Fe phase or R2T phase is usually generated in the grain boundary phase 14. 17 Equal soft magnetic phase, so that H cJ However, if the B content is less than R2T 14 The stoichiometric ratio of the B compound and the metal element M selected from Al, Ga, and Cu are formed by R2T 17 The transition metal-rich phase (such as RT-Ga phase) is generated to increase the thickness of the grain boundary between the two grains, and as a result, high H cJ .
[0041] In RTB-based sintered magnets, in order to increase the thickness of the grain boundary between two crystal grains, it is important to control not only the B content but also the oxygen content. After research, the inventors found that in the manufacturing process of the powder molded body obtained by crushing the magnet alloy as the raw material, in order to accurately control the oxygen content in the raw material of the RTB-based sintered magnet within a set range, it is important to place the micro-milled powder that has just been prepared by the crushing device and is in the most easily oxidized active state in an oil agent with an adjusted water content, thereby inhibiting oxidation caused by moisture. In an embodiment of the present invention, the water content of the oil agent is not simply reduced, but the water content of the oil agent is managed and controlled according to the quality of the powder in the oil agent, so that the oxidation of the powder can be more effectively controlled.
[0042] <Implementation Method>
[0043] Next, refer to Figure 2 The following is an overview of a method for producing a rare earth sintered magnet according to an embodiment of the present invention. Figure 2 As shown, the manufacturing method of the rare earth sintered magnet in this embodiment includes a step (S10) of crushing a rare earth raw material alloy to prepare the above-mentioned rare earth raw material alloy powder; a step (S12) of recovering the above-mentioned powder using a recovery container; a step (S14) of supplying oil to the above-mentioned recovery container through a pipeline filled with inert gas before or after recovering the above-mentioned powder, or during the recovery, and a step (S16) of adjusting the ratio of the mass of water in the above-mentioned oil supplied to the above-mentioned recovery container to the mass of the above-mentioned powder recovered, that is, the water ratio, to less than 0.005%.
[0044] The important point of the manufacturing method of the embodiment of the present invention is that the ratio of the mass of water in the oil solution supplied to the recovery container to the mass of the recovered powder, i.e., the water ratio, is adjusted to 0.005% or less. The technical effect of this will be described later.
[0045] The above steps are described below.
[0046] <Rare Earth Alloy Powder Preparation Step (S10)>
[0047] In this embodiment, as a process (fine grinding process) of grinding the raw alloy to obtain rare earth alloy powder, the process S10 of preparing rare earth alloy powder by a jet mill grinding device is used. Preferably, before the process S10, a hydrogen crushing process is performed to prepare a coarse crushed powder of the rare earth alloy. The composition of the raw rare earth alloy is as follows. It includes:
[0048] R: 26.5 to 33.5 mass % (R is a rare earth element, but it must contain at least one of Nd and Pr),
[0049] M: 0.20 to 1.50 mass % (M is at least one selected from Ga, Cu, Zn, Al and Si, and must contain Cu),
[0050] B: 0.85-0.92% by mass
[0051] T: 61.5 mass % or more, (T is Fe and Co, and 90% or more of T is Fe in terms of mass ratio),
[0052] and,
[0053] Tb: 0.30 mass% or less, and
[0054] Dy: 0.30 mass % or less.
[0055] By adjusting the B content to the above range, R6T is formed at the grain boundaries of the rare earth sintered magnet. 13 Ga and thickening the grain boundaries between the two grains, it is possible to achieve, for example, a B of 1.39T or more. r and high H above 1640kA / m cJ In order to ensure thickening of the grain boundaries between the two crystal grains, the molar ratio of T ([T] / [B]) is more preferably higher than 14.0 and lower than 15.0.
[0056] The rare earth alloy raw material having the above composition can be prepared by, for example, a thin strip continuous casting method. The rare earth alloy can include a plurality of alloy components with different compositions. By making the whole have the above composition, it is possible to achieve thickening of the above two grain boundaries and achieving high H cJ effect.
[0057] The hydrogen crushing process may include a hydrogen storage process in which hydrogen is stored in the above-mentioned rare earth alloy at a temperature below 200°C in a processing chamber; and a dehydrogenation process in which hydrogen is discharged from the processing chamber, the rare earth alloy is heated in a range of, for example, above 80°C and below 650°C, and a dehydrogenation treatment is performed to prepare a coarsely crushed powder.
[0058] The average particle size of the coarsely crushed powder is, for example, 10 μm or more and 500 μm or less. It should be noted that the average particle size (d50) in the present invention can be measured by airflow dispersion laser diffraction method (according to JIS Z 8825: 2013 revised edition). That is, in this specification, the average particle size refers to the particle size (median particle size: d50) when the cumulative particle size distribution (volume basis) calculated from the small particle size side reaches 50%.
[0059] In the step (S10) of the fine pulverization step, the coarsely crushed powder can be pulverized to obtain a fine powder having a median particle size d50 of, for example, 3.5 μm or less. The fine pulverization step may include a step of mixing an organic grinding aid with the coarsely crushed powder. As the organic grinding aid, for example, zinc stearate can be cited. The average particle size d50 of the finely crushed powder is preferably 2.0 μm or more and 3.5 μm or less.
[0060] Next, refer to Figure 3 An example of a pulverizing system including a jet mill pulverizing device and a recovery container will be described. Figure 3 Schematic diagram of a structural example of a pulverizing system 1000 according to an embodiment of the present invention. In this example, the pulverizing system 1000 includes a jet mill pulverizing device 100, a cyclone collector 200, a bag filter 300, a recovery container 400, and an oil supply device 500.
[0061] The jet mill pulverizing device 100 receives the supply of the material to be pulverized from the raw material tank (not shown) via the raw material input pipe 34. A plurality of valves are provided on the raw material input pipe 21, and the jet mill pulverizing device 100 maintains an appropriate internal pressure by opening and closing the valves. The material to be pulverized introduced into the jet mill pulverizing device 100 collides with the collision plate provided for efficiently performing mutual collision and pulverization of the material to be pulverized by the high-speed injection of the inactive gas from the nozzle pipe 31, and is ground into fine powder.
[0062] Rare earth alloy powders such as RTB alloy for sintered magnets are active and easily oxidized. Therefore, in order to avoid the risk of heat and fire, reduce the content of oxygen as an impurity to achieve high performance of the magnet, the gas used in the jet mill pulverizing device 100 is usually an inactive gas such as dried (high purity) nitrogen, argon, helium, etc. with a dew point of less than -60°C dp.
[0063] The powder particles (finely pulverized powder) finely ground inside the jet mill pulverizing device 100 are guided to the inlet pipe 22 of the cyclone separator collection device 200 from the upper discharge port by the rising air flow. The coarse particles that are not fully pulverized can also be sorted by, for example, a classification rotator provided for classifying coarse particles larger than the median particle size (d50), and remain in the jet mill pulverizing device 100 to undergo a further pulverization process using collision. Such classification of coarse particles can also be performed using centrifugal separation using eddy currents instead of using a classification rotator. In this way, the coarsely crushed powder input into the jet mill pulverizing device 100 is pulverized into finely pulverized powder having a particle size distribution with an average particle size (median particle size: d50) of, for example, 2.0 μm or more and 4.5 μm or less, and then transported to the cyclone separator collection device 200.
[0064] The cyclone collector 200 is used to separate the powder from the airflow carrying the powder. Specifically, the coarse crushed powder of the alloy for RTB-based sintered magnet is crushed by a pre-stage jet mill, and the finely crushed powder generated by the crushing is supplied to the cyclone collector 200 through the inlet pipe 22 together with the gas used for crushing. The mixture of the inactive gas (crushing gas) and the crushed finely crushed powder forms a high-speed airflow and is sent to the cyclone collector 200. The cyclone collector 200 is used to separate these crushing gases from the finely crushed powder. The finely crushed powder separated from the crushing gas is recovered by the recovery container (recovery device) 400 through the pipe 24 connected to the exhaust port 40. It should be noted that the crushing gas is supplied to the bag filter device 300 through the outlet pipe 23 of the cyclone collector 200. Very small fine particles are recovered in the bag filter device 300, and clean gas is discharged to the outside from the exhaust port 25. It should be noted that, for such solid-gas separation, a bag filter may be used instead of the cyclone collector 200, but damage to the filter may cause the finely pulverized powder to fly into the atmosphere, which has a great impact on the environment and safety. Figure 3 As shown in the example, a bag filter is further used in combination to separate fine particles from the gas separated by the cyclone collector 200.
[0065] The dew point in the pulverizing chamber and the amount supplied to the jet mill pulverizing device also depend on the pulverizing time and the size of the jet mill pulverizing device, but in some preferred embodiments, the inert gas can adjust the dew point during pulverizing to above -55°C dp and below -30°C dp. Examples of inert gases are nitrogen, argon, and helium. Among them, nitrogen is the most preferred because it is a high-purity gas that can be obtained at a low cost. Therefore, in a preferred embodiment, the inert gas is nitrogen.
[0066] exist Figure 3 In the pulverizing system 1000 shown, the pipeline 24 for transferring the finely pulverized powder produced by the jet mill pulverizing device 100 to the recovery container 400 is provided in the cyclone separator collection device 200. In the absence of the cyclone separator collection device 200, such a pipeline 24 can be directly provided in the jet mill pulverizing device 100. Figure 3 In the example, an air intake pipe 32 is provided which communicates with the inside of the pipe 24. The air intake pipe 32 may be provided at the upper portion of the recovery container 400. By supplying inert gas from the inert gas supply unit 42 to the air intake pipe 32, the inside of the pipe 24 and the inside of the recovery container 400 can be filled with inert gas.
[0067] <Step of recovering powder using recovery container (S12)>
[0068] By using the pulverizing system 1000 having the above-mentioned composition, the finely pulverized powder produced by the jet mill pulverizing device 100 can be transported to the recovery container 400 filled with inert gas through the pipe 24 filled with inert gas.
[0069] In this embodiment, as the inert gas supplied to the air intake pipe 32, a dry gas (e.g., dry nitrogen) having a dew point of more than -80°C dp and less than -30°C dp can be used. Since the finely pulverized powder is transported to the recovery container 400 in the state of the pipe 24 and the recovery container 400 filled with such an inert gas, the finely pulverized powder can be recovered without contacting with water vapor in the atmosphere. In this way, the oxygen concentration in the rare earth alloy powder will not increase due to water vapor in the manufacturing process, but can be precisely controlled within a predetermined range. As a result, the grain boundary phase of the final rare earth sintered magnet can be adjusted to an appropriate range to achieve the desired grain boundary thickness between the two crystal grains.
[0070] The air intake pipe 32 of the present embodiment is preferably made of a flexible non-metallic material. If the air intake pipe 32 is formed of a rigid material such as a metal material, the presence of the air intake pipe 32 makes it difficult to remove the powder (finely pulverized powder) that has been transported to the recovery container 400 and to repair the pulverizing system 1000. The air intake pipe 32 is preferably made of fluororesin. Since fluororesin has a low permeability to water vapor, it is possible to suppress the water vapor in the atmosphere from flowing through the air intake pipe 32 into the interior of the above-mentioned pipe 24 and the recovery container 400. As a result, it is possible to achieve the effect of maintaining the dew point inside the pipe 24 and the recovery container 400 below -30°C dp.
[0071] According to the research of the present inventors, for example, when an inert gas is supplied to the inside of the pipe 24 and the recovery container 400 using an intake pipe formed of polyurethane, water vapor in the atmospheric environment oxidizes the powder recovered by the recovery container 400 through the intake pipe. Therefore, even if the dew point of the inert gas inside the inert gas supply part 42 is adjusted to above -80°C dp and below -30°C dp, it may be difficult to maintain the dew point inside the pipe 24 and the recovery container 400 above -80°C dp and below -30°C dp. According to an embodiment of the present invention, since the intake pipe 32 is formed of a fluororesin through which water vapor has difficulty passing, when the inert gas is supplied by the intake pipe 32, the dew point inside the pipe and the recovery container can be maintained above -80°C dp and below -30°C dp. Therefore, according Figure 3 The pulverizing system 1000 can carry out the process of conveying the finely pulverized powder from the jet mill pulverizing device 100 to the recovery container 400 through the pipe 24 while maintaining the dew point inside the pipe 24 and the recovery container 400 at above -80°C dp and below -30°C dp.
[0072] <Step of Supplying Oil to Recovery Container (S14)>
[0073] The pulverizing system 1000 in the present embodiment further includes an oil agent supply device 500 for supplying oil agent to the recovery container 400. The oil agent supply device 500 is connected to the recovery container 400 via a pipe 36.
[0074] The timing of supplying the oil to the recovery container 400 may be before or after the powder is recovered, or during the recovery period. The oil may be stored in the recovery container 400 in advance before the powder is transferred to the recovery container 400 through the pipe 24. In this case, the supplied powder sinks into the oil stored in the recovery container 400. Since the contact between the powder in the oil and the ambient gas is blocked, direct oxidation caused by oxygen or water vapor in the atmosphere can be suppressed.
[0075] However, according to the research of the inventors, it was found that as the storage time of the powder in the oil agent increases, the powder will be oxidized by the moisture in the oil agent, and the oxygen concentration of the powder will increase. For this reason, in an embodiment of the present invention, the oxidation of the powder is suppressed by controlling the water content of the oil agent. Specifically, it can be adjusted by, for example, introducing an inert gas into the oil agent stored in the recovery container 400 to reduce the mass of water in the oil agent. It should be noted that, since the powder inside the recovery container 400 is in an oil agent whose moisture concentration is controlled within a set range, even if the powder is retained in the recovery container 400 for a long time (for example, more than 60 minutes), the oxidation of the powder will be suppressed, and the increase in the oxygen content (oxygen concentration) in the final rare earth sintered magnet can be suppressed. The recovery container 400 can also be configured as a structure that can be loaded and unloaded from the pulverizing system 1000.
[0076] In the present embodiment, the water content of the oil is not simply reduced, but the ratio of "the mass of water in the oil" to "the mass of the powder (recovered powder) in the oil", that is, the water ratio, is adjusted to less than 0.005%. This is because the oxidation of the powder in the oil depends not only on the mass of water in the oil, but also on the mass of the powder present in the oil (the mass of the recovered powder). When the water ratio exceeds 0.005%, the powder blocked from the atmosphere by the oil will be oxidized by the water dissolved in the oil. The oxidation proceeds as the time the powder stays in the oil increases. According to the present embodiment, even if the powder remains in the oil for a long time (for example, more than 1 hour), the increase in the oxygen content of the final rare earth sintered magnet can be suppressed. Preferably, the above-mentioned water ratio is less than 0.003%. It should be noted that the above-mentioned water ratio can be measured using a known water content meter in oil, such as TEKHNEPort-Oil manufactured by TEKHNE Corporation.
[0077] <Oil-water ratio adjustment step (S16)>
[0078] The water content of the oil can be adjusted by introducing an inert gas into the oil stored in the tank of the oil supply device 500 to reduce the water content in the oil. In this embodiment, the "water ratio" of the water content in the oil to the mass of the powder transferred from the jet mill pulverizing device 100 to the recovery container 400 is adjusted to 0.005% or less. The pulverizing system 1000 having the above-mentioned configuration can perform the above-mentioned steps S12, S14, and S16.
[0079] Next refer to Figure 4 . The method for manufacturing a rare earth sintered magnet of the present embodiment includes a step (S18) of preparing a powder compact from the powder (finely pulverized powder) recovered from the recovery container 400, and a step (S20) of sintering the powder compact to prepare a rare earth sintered magnet material. Preferably, it also includes a step (S22) of preparing a diffusion source powder formed of an RMA alloy; and a step (S24) of heat-treating the diffusion source powder while it is attached to the surface of the rare earth sintered magnet material to diffuse the elements contained in the diffusion source powder into the interior of the rare earth sintered magnet material.
[0080] The following is a description of each of the above-mentioned process examples.
[0081] <Step of Preparing a Powder Molded Body (S18)>
[0082] The powder molded body can be made from powder (finely pulverized powder) by, for example, pressing in a magnetic field. From the perspective of suppressing oxidation, when pressing in a magnetic field, it is preferred to form the powder molded body by pressing in an inert gas environment or wet pressing. In particular, in wet pressing, the surface of the particles constituting the powder molded body is coated with a dispersant such as an oil agent, which suppresses contact with oxygen and water vapor in the atmosphere. Therefore, it is possible to prevent or suppress oxidation of the particles by the atmosphere before or after the pressing process or during the pressing process.
[0083] When wet pressing is performed in a magnetic field, a slurry in which a dispersion medium is mixed in a finely pulverized powder is prepared, supplied to the mold cavity of a mold of a wet pressing device, and pressed in a magnetic field. The dispersion medium is a liquid that can obtain a slurry by dispersing the alloy powder inside it. As a preferred dispersion medium used in the present invention, mineral oil or synthetic oil can be cited. The type of mineral oil or synthetic oil is not specific, but when the kinematic viscosity at room temperature exceeds 10 cSt, the mutual binding force of the alloy powder will increase due to the increase in viscosity, which may have an adverse effect on the orientation of the alloy powder during wet molding in a magnetic field. Therefore, the kinematic viscosity of the mineral oil or synthetic oil at room temperature is preferably less than 10 cSt. And when the fractionation temperature of the mineral oil or synthetic oil exceeds 400 ° C, it is difficult to deoil after obtaining the molded body, the amount of residual carbon in the sintered body increases, and the magnetic properties may decrease. Therefore, the fractionation temperature of the mineral oil or synthetic oil is preferably below 400 ° C. In addition, vegetable oil can be used as a dispersion medium. Vegetable oil refers to oil extracted from plants, and the plant species are not limited to specific plants.
[0084] The obtained alloy powder can be mixed with a dispersion medium to obtain a slurry. The mixing ratio of the alloy powder and the dispersion medium is not particularly limited, and the concentration of the alloy powder in the slurry is preferably 70% or more (i.e., 70% by mass or more) in terms of mass ratio. This is because the concentration of the alloy powder in the slurry is 70% or more in the range of 20 to 600 cm 3 At a flow rate of 1000 g / min, not only can the alloy powder be efficiently supplied to the inside of the mold cavity, but also excellent magnetic properties can be obtained. The alloy powder concentration in the slurry is preferably less than 90% by mass ratio. There is no particular restriction on the mixing method of the alloy powder and the dispersion medium. The alloy powder and the dispersion medium can be prepared separately, and the two are weighed and mixed according to a predetermined amount to make. In addition, when the coarse crushed powder is dry-crushed to obtain the alloy powder by a jet mill, a container equipped with a dispersion medium is arranged at the alloy powder discharge port of the pulverizing device such as a jet mill, and the alloy powder obtained by crushing is directly recovered in the dispersion medium in the recovery container to obtain a slurry. In this case, it is preferred to set the recovery container to an environment composed of nitrogen and / or argon, and the obtained alloy powder is directly recovered from the dispersion medium in a state without contact with the atmosphere to form a slurry. In addition, the coarse crushed powder can also be kept in the dispersion medium by using a vibration mill, a ball mill or a stirred mill to perform wet crushing to obtain a slurry composed of alloy powder and a dispersion medium.
[0085] By molding the slurry thus obtained using a known wet pressing apparatus, a molded body having a predetermined size and shape can be obtained. The molded body is sintered to obtain a sintered body.
[0086] <Step of Preparing Rare Earth Sintered Magnet Material (S20)>
[0087] Next, the powder compact is fired to obtain a rare earth sintered magnet (sintered body).
[0088] The sintering of the powder molded body is preferably carried out in the range of 1000°C to 1150°C. In order to prevent oxidation caused by sintering, the residual gas in the environment can be replaced with an inert gas such as helium or argon. The obtained sintered body is preferably heat-treated. The magnetic properties can be improved by heat treatment. The heat treatment conditions such as heat treatment temperature and heat treatment time can adopt known conditions. The rare earth sintered magnet obtained in this way can be subjected to a grinding / polishing process, a surface treatment process and a magnetization process as needed to complete the final rare earth sintered magnet.
[0089] <Step of Preparing Diffusion Source Powder (S22)>
[0090] In the diffusion source RMA alloy, R contains at least one rare earth element and contains at least one of Nd and Pr. M is at least one selected from Cu, Ga, Co and Fe. A is at least one selected from Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag and B.
[0091] The composition ratio of R is 65 mass % or more and 95 mass % or less of the entire RMA alloy, the composition ratio of M is 5 mass % or more and 35 mass % or less of the entire RMA alloy, and the composition ratio of A is 0 mass % or more and 3 mass % or less of the entire RMA alloy.
[0092] The diffusion source can be prepared by using a raw material alloy preparation method used in a common manufacturing method represented by Nd-Fe-B system sintered magnet, such as a mold casting method, a thin strip continuous casting method, a single roll super quenching method (melt spinning method), an atomization method, etc. In addition, the diffusion source can also be a pulverized product obtained by pulverizing the alloy obtained above by a known pulverizing device such as a pin mill. In addition, in order to improve the pulverizability of the alloy obtained by the above method, a heat treatment below 700°C can be performed in a hydrogen environment to allow the material to contain hydrogen before pulverization.
[0093] <Diffusion Step of Elements Contained in Diffusion Source Powder (S24)>
[0094] By performing heat treatment at a temperature of 700°C to 1100°C in a vacuum or inert gas environment, the elements contained in the diffusion source are diffused from the surface of the sintered body to the inside. In the present invention, this heat treatment is referred to as the first heat treatment. When the heat treatment temperature for diffusion is lower than 700°C, the diffusion may be insufficient and high H may not be obtained. cJ On the other hand, when the temperature exceeds 1100°C, abnormal grain growth occurs in the main phase, and H cJ The heat treatment temperature for diffusion is preferably 800°C or higher and 1000°C or lower. This is because a higher H cJIt should be noted that the heat treatment time can be set to an appropriate value according to the composition, size, heat treatment temperature, etc. of the sintered material and the diffusion source, preferably more than 5 minutes and less than 30 hours, more preferably more than 10 minutes and less than 25 hours, and further preferably more than 30 minutes and less than 20 hours. In addition, it is preferred to prepare a diffusion source of more than 1 mass % and less than 30 mass % relative to the weight of the sintered material. When the diffusion source is less than 1 mass % relative to the weight of the sintered material, H cJ On the other hand, if it exceeds 30% by mass, B r It is possible to reduce.
[0095] The heat treatment for diffusion can be performed using a known heat treatment method. For example, the first heat treatment can be performed by covering the surface of the sintered body material with a powder layer of the diffusion source. For example, the first heat treatment can be performed after the diffusion source is applied to the surface of the sintered body material by sputtering. For example, the diffusion source can also be applied to the surface of the sintered material by evaporating the dispersion medium after a slurry in which the diffusion source is dispersed in a dispersion medium is applied to the surface of the sintered material. It should be noted that as dispersion media, alcohols (ethanol, etc.), NMP (N-methylpyrrolidone), aldehydes and ketones can be cited as examples. In addition, the sintered body material that has been subjected to the first heat treatment can also be subjected to known mechanical processing such as cutting and machining.
[0096] The sintered material after the heat treatment for diffusion can be heat treated at a temperature of 450°C to 600°C in a vacuum or inert gas environment. In the present invention, this heat treatment is referred to as the second heat treatment. By performing the second heat treatment, a high B r and high H cJ By setting the second heat treatment temperature to 450°C or higher and 600°C or lower, R6T can be performed. 13 The second heat treatment temperature is preferably 480°C or higher and 560°C or lower. cJ It should be noted that the heat treatment time can be set to an appropriate value according to the composition, size, heat treatment temperature, etc. of the sintered body material, and is preferably 5 minutes or more and 20 hours or less, more preferably 10 minutes or more and 15 hours or less, and further preferably 30 minutes or more and 10 hours or less.
[0097] According to this embodiment, the finely ground powder in the most oxidizable active state immediately after being produced by the jet mill can be prevented from being oxidized by the water in the oil in the recovery container. As a result, a rare earth sintered magnet with modified grain boundaries can be obtained.
[0098] Example
[0099] The present invention will be described in more detail below through experimental examples, but the present invention is not limited thereto.
[0100] Experimental Example 1
[0101] A rare earth raw material alloy (RTB sintered magnet alloy) as shown in Table 1 Sample No. 1 was prepared. Specifically, an alloy of each element was prepared according to the composition shown in Table 1 Sample No. 1, and the RTB sintered magnet alloy was prepared by a thin strip continuous casting method. The obtained RTB sintered magnet alloy was coarsely crushed by hydrogen crushing to obtain coarse crushed powder. The coarse crushed powder was put into Figure 3 The coarsely crushed powder was crushed by a jet mill pulverizing device 100 to obtain fine powder. The average particle size (d50) of the obtained fine powder was 3.0 μm. The average particle size (d50) was measured in a particle size distribution measuring device "HELOS & RODOS" manufactured by Sympatec under the conditions of dispersion pressure: 4 bar, range: R2, and calculation mode: HRLD.
[0102] The obtained fine powder is stored in advance from Figure 3 The oil supplied in the tank of the oil supply device 500 is recovered in the recovery container 400. The moisture ratio of the ratio of the mass of water in the above-mentioned oil supplied to the above-mentioned recovery container to the mass of the powder in the above-mentioned oil before recovery is adjusted as shown in Table 2. The moisture ratio was measured using the TEKHNE Port-Oil moisture meter for oil production of TEKHNE Corporation. Then, after the fine powder was stored in the recovery container 400 for 60 minutes, the above-mentioned fine powder was immersed in mineral oil under a nitrogen environment to form a slurry. The slurry concentration is 75% by mass. The obtained slurry is molded in a magnetic field (wet molding) to obtain a molded body. It should be noted that the molding device adopts a so-called right-angle magnetic field molding device (transverse magnetic field molding device) in which the direction of the external magnetic field is orthogonal to the compression direction.
[0103] The obtained molded body was sintered in vacuum at 1050°C (a temperature selected to achieve sufficient densification by sintering) for 4 hours to obtain a sintered body. The density of the sintered body was 7.5 Mg / m 3The above. The sintered body was heat treated by keeping it at 800°C for 2 hours and then cooling it to room temperature, and then keeping it at 500°C for 2 hours and then cooling it to room temperature, to obtain RTB system sintered magnets (No. 1 to 5). The O (oxygen content) of the obtained sintered magnets was measured using the gas melting-infrared absorption method. The results are shown in Table 2. In addition, instead of storing the fine powder in the recovery container 400 for 60 minutes, the fine powder recovered from the recovery container 400 was directly immersed in mineral oil under a nitrogen environment to form a slurry, and the same operation as No. 1 to 5 was performed to produce RTB system sintered magnets (No. A). After measuring the oxygen content of the finished product, it was found that the oxygen content was 0.095% by mass. The difference in oxygen content (Δ oxygen content) between the RTB system sintered magnet No. A and the RTB system sintered magnet No. 1 to 5 is shown in Table 2.
[0104] [Table 1]
[0105]
[0106] [Table 2]
[0107]
[0108] As shown in Table 2, the oxygen content of the examples of the present invention (No. 1, 4, 5) was lower than that of the comparative examples (No. 2, 3), and the Δ oxygen content was also controlled to be less than 400 ppm.
[0109] As described above, the present invention relates to a method for producing a rare earth system sintered magnet as described in the following items.
[0110] [Item 1]
[0111] A method for producing a rare earth sintered magnet, comprising:
[0112] A step of pulverizing a rare earth alloy raw material to prepare a powder of the rare earth alloy raw material;
[0113] The process of recovering the powder using a recovery container;
[0114] A step of supplying an oil solution to the recovery container before or after the recovery of the powder, or during the recovery; and
[0115] A step of adjusting the water ratio, which is the ratio of the mass of the water in the oil solution supplied to the recovery container to the mass of the recovered powder in the oil solution, to 0.005% or less.
[0116] [Item 2]
[0117] In the method for producing a rare earth sintered magnet according to item 1, the step of adjusting the water content to 0.005% or less includes the step of introducing an inert gas into the oil to reduce the amount of water in the oil.
[0118] [Item 3]
[0119] The method for producing a rare earth sintered magnet according to item 2, wherein:
[0120] The step of preparing the powder includes the step of pulverizing the rare earth raw material alloy by a jet mill pulverizing device, and the step of supplying an inert gas to the inside of a pipe connecting the jet mill pulverizing device and the recovery container and to an air inlet pipe communicating with the inside of the recovery container; and
[0121] The step of conveying the powder from the jet mill pulverizing device through the pipeline filled with the inert gas to the recovery container filled with the inert gas and the oil agent,
[0122] The dew point inside the pipeline and the recovery container is maintained above -80°C dp and below -30°C dp.
[0123] [Item 4]
[0124] The method for producing a rare earth sintered magnet according to item 3, wherein the air intake pipe is made of fluororesin.
[0125] [Item 5]
[0126] According to the method for producing a rare earth sintered magnet as described in item 4, a cyclone classifier is provided at the rear stage of the jet mill pulverizing device, and the duct connects the cyclone classifier and the recovery container.
[0127] [Item 6]
[0128] The method for producing a rare earth sintered magnet according to any one of items 1 to 5, wherein the rare earth raw material alloy has a composition comprising:
[0129] R: 26.5 to 33.5 mass % (R is a rare earth element, but it must contain at least one of Nd and Pr),
[0130] M: 0.20 to 1.50 mass % (M is at least one selected from Ga, Cu, Zn, Al and Si, and must contain Cu),
[0131] B: 0.85-0.92% by mass
[0132] T: 61.5 mass % or more, (T is Fe and Co, and 90% or more of T is Fe in terms of mass ratio),
[0133] and,
[0134] Tb: 0.30 mass% or less, and
[0135] Dy: 0.30 mass % or less.
[0136] [Item 7]
[0137] The method for producing a rare earth sintered magnet according to item 6, further comprising:
[0138] A step of preparing a powder compact from the powder recovered in the recovery container;
[0139] The step of sintering the powder compact to prepare a rare earth sintered magnet material;
[0140] a step of preparing a diffusion source powder formed of an RMA alloy; and
[0141] a step of performing heat treatment while the diffusion source powder is attached to the surface of the rare earth system sintered magnet material to diffuse the elements contained in the diffusion source powder into the interior of the rare earth system sintered magnet material;
[0142] In the above RMA alloys,
[0143] R is at least one rare earth element and includes at least one of Nd and Pr,
[0144] M is at least one selected from Cu, Ga, Co and Fe,
[0145] A is at least one selected from Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag and B,
[0146] The composition ratio of R is 65 mass % or more and 95 mass % or less of the entire RMA alloy.
[0147] The composition ratio of M is 5 mass % or more and 35 mass % or less of the entire RMA alloy.
[0148] The composition ratio of A is not less than 0 mass % and not more than 3 mass % of the entire RMA alloy.
Claims
1. A method for producing a rare earth sintered magnet, wherein: include: A step of pulverizing a rare earth alloy raw material to prepare a powder of the rare earth alloy raw material; The step of recovering the powder using a recovery container; Before or after the powder is recovered, or during the recovery, supplying oil to the recovery container; and A step of adjusting the water ratio, which is the ratio of the mass of the water in the oil solution supplied to the recovery container to the mass of the recovered powder in the oil solution, to 0.005% or less.
2. The method for producing a rare earth sintered magnet according to claim 1, wherein: The step of adjusting the water content to 0.005% or less includes the step of introducing an inert gas into the oil to reduce the amount of water in the oil.
3. The method for producing a rare earth sintered magnet according to claim 2, wherein: The step of preparing the powder includes the step of pulverizing the rare earth alloy raw material by a jet mill pulverizing device, and further includes: The step of supplying an inert gas to the interior of a pipe connecting the jet mill pulverizing device and the recovery container and to an air intake pipe communicating with the interior of the recovery container; and The step of conveying the powder from the jet mill pulverizing device through the pipe filled with the inert gas to the recovery container filled with the inert gas and the oil agent, The dew point inside the pipeline and the recovery container is maintained above -80°C dp and below -30°C dp.
4. The method for producing a rare earth sintered magnet according to claim 3, wherein: The air intake pipe is made of fluororesin.
5. The method for producing a rare earth sintered magnet according to claim 4, wherein: A cyclone classifier is provided at the rear section of the jet mill pulverizing device, and the pipeline connects the cyclone classifier and the recovery container.
6. The method for producing a rare earth sintered magnet according to any one of claims 1 to 5, wherein: The composition of the rare earth raw material alloy comprises: R: 26.5-33.5% by mass, wherein R is a rare earth element, but it must contain at least one of Nd and Pr, M: 0.20-1.50 mass %, wherein M is at least one selected from Ga, Cu, Zn, Al and Si, and must contain Cu, B: 0.85-0.92% by mass T: 61.5 mass % or more, wherein T is Fe and Co, and in terms of mass ratio, 90% or more of T is Fe, and, Tb: 0.30 mass% or less, and Dy: 0.30 mass % or less.
7. The method for producing a rare earth sintered magnet according to claim 6, wherein: Also includes: A step of preparing a powder compact from the powder recovered in the recovery container; The step of sintering the powder compact to prepare a rare earth sintered magnet material; a step of preparing a diffusion source powder formed of an RMA alloy; and a step of performing heat treatment while the diffusion source powder is attached to the surface of the rare earth system sintered magnet material to diffuse elements contained in the diffusion source powder into the interior of the rare earth system sintered magnet material; In the RMA alloy, R is at least one rare earth element and includes at least one of Nd and Pr, M is at least one selected from Cu, Ga, Co and Fe, A is at least one selected from Al, Si, Ti, V, Cr, Mn, Co, Ni, Zn, Ge, Zr, Nb, Mo, Ag and B, The composition ratio of R is 65 mass % or more and 95 mass % or less of the entire RMA alloy. The composition ratio of M is 5 mass % or more and 35 mass % or less of the entire RMA alloy. The composition ratio of A is not less than 0 mass % and not more than 3 mass % of the entire RMA alloy.
Citation Information
Patent Citations
Alloy for r-t-b-based rare earth sintered magnet, process for producing alloy for r-t-b-based rare earth sintered magnet, alloy material for r-t-b-based rare earth sintered magnet, r-t-b-based rare earth sintered magnet, process for producing r-t-b-based rare earth sintered magnet, and motor
WO2013008756A1